2022
DOI: 10.1038/s10038-022-01041-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal microarray analysis versus noninvasive prenatal testing in fetuses with increased nuchal translucency

Abstract: Objective To evaluate if the NT value of 2.5 mm ≤ NT < 3.0 mm is an appropriate indication for CMA tests among fetuses with isolated increased NT and NIPT is more suitable instead. Methods A total of 442 fetuses with NT ≥ 2.5 mm were included, in which 241 fetuses underwent karyotype. CMA tests were then carried out when cytogenic analysis showed normal chromosomes and CNV status was compared between 2.5 mm ≤ NT < 3.0 mm and ≥3.0 mm subgroups. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The detection rates of aneuploidy and CNVs in fetuses with NT 95th percentile-2.99 mm were high, while the incremental yield of monogenic disorders was 0%. Therefore, we suggest, as most of the literature (Wang et al, 2022;Xie et al, 2022;Yin et al, 2022) To assess the risk of chromosomal abnormalities in fetuses with NT of 3.0-3.49 mm and to determine whether invasive prenatal testing is necessary, our results showed an 11.7% risk of chromosomal abnormalities (including aneuploidy and pCNVs). The study by Petersen et al (2020) performed a meta-analysis of literature cases with NT of 3.0-3.49 mm and a retrospective study of two groups of pregnant women with invasive testing and CMA, which showed 13.5% of 522 fetuses were diagnosed with chromosomal aberrations, similar to the results of our study.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The detection rates of aneuploidy and CNVs in fetuses with NT 95th percentile-2.99 mm were high, while the incremental yield of monogenic disorders was 0%. Therefore, we suggest, as most of the literature (Wang et al, 2022;Xie et al, 2022;Yin et al, 2022) To assess the risk of chromosomal abnormalities in fetuses with NT of 3.0-3.49 mm and to determine whether invasive prenatal testing is necessary, our results showed an 11.7% risk of chromosomal abnormalities (including aneuploidy and pCNVs). The study by Petersen et al (2020) performed a meta-analysis of literature cases with NT of 3.0-3.49 mm and a retrospective study of two groups of pregnant women with invasive testing and CMA, which showed 13.5% of 522 fetuses were diagnosed with chromosomal aberrations, similar to the results of our study.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, in 259 fetuses with a NT 95th percentile-2.99 mm, CMA detected 13 CNVs that were not detectable by conventional karyotyping, including only three pCNVs (1.16%). In the previous studies, Wang et al (2022) found that chromosomal aneuploidy and genomic imbalance were the primary fetal abnormalities when NT was 2.5-3.0 mm and that for fetuses with increased isolated NT between 2.5 and 3.0 mm, NIPT (3.98%) had a similar rate of karyotype detection (5%) in a study of 201 fetuses with examined by NIPT and karyotype. Xie et al (2022) applied NIPT-Plus to 72 fetuses with increased NT and achieved a sensitivity and specificity of 95.2% and 100% for common chromosomal aneuploidy, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The incidence also exceeds 6% in fetuses with structural abnormalities by ultrasound test but normal chromosome karyotypes. [9][10][11] During early pregnancy screening, invasive amniocentesis or chorionic villus sampling (CVS) is used after biochemical and ultrasound studies show potential abnormal fetal development to obtain prenatal samples for chromosome karyotype analysis and chromosome microarray analysis (CMA), which is the gold standard of prenatal diagnosis. [12,13] Karyotype analysis can detect structural abnormalities such as an abnormal number of chromosomes as well as deletions, duplications, inversions, and translocations larger than 10 Mb (at least 5 Mb).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence also exceeds 6% in fetuses with structural abnormalities by ultrasound test but normal chromosome karyotypes. [ 9 11 ]…”
Section: Introductionmentioning
confidence: 99%